Development of Polyps and Cancer in Patients with a Negative Colonoscopy: A Follow-Up Study of More Than 20 Years. (4th March 2014) - Loffeld, R. J. L. F.
Abstract : Background. Adenomas are missed during colonoscopy. Aim. Assess the occurrence of colorectal cancer (CRC) and polyps in patients with a negative index colonoscopy (IC). Patients and Methods. All patients with a IC in 1992–1994, aged 40 and 60 years, were included. Exclusion criterion was presence of abnormalities, a family history, or surveillance. At the end of 2013 all records were studied in order to gather follow-up information. Results. 394 patients were included in four groups: group 1 patients who died, group 2 patients who were not in the hospital systems anymore, group 3 patients still visiting the hospital but not the department of gastroenterology, and group 4 patients undergoing new colonoscopies. In group 1, 2 patients died of CRC and 4 developed a polyp. No data were available from the patients in group 2. Patients in group 3 visited the outpatient clinics but did not undergo new colonoscopy. Patients in group 4 underwent additional colonoscopies. The yield was 35 patients polyps and three CRCs. Five patients (1.3%) developed CRC, and 39 (9%) developed a polyp. Conclusion. Given these results the number of potentially missed adenomas in IC is very low and the consequences of missed adenomas are highly exaggerated.